Efektivitas Kombinasi Natrium Hipoklorit dengan Lansoprazole dalam Menghambat Enterococcus faecalis dan Eschericia coli - Geralda Santjoko, Gabriella; Nugroho Santosa, Didi (Jurnal Kedokteran Gigi Terpadu, 2022)
Background: Sodium hypochloride (NaOCl), which is the gold standard for irrigation solutions, has low bactericidal activity against Enterococcus faecalis, the main cause of root canal treatments failure. This resistance due to its proton pump, which can also be found in Escherichia coli. This research was conducted using a combination of NaOCl with lansoprazole, the latest generation proton pump inhibitor. Objective: To determine the antibacterial effect of the combination of NaOCl with various concentrations of lansoprazole against E. faecalis and E. coli. Method: Laboratory experimental research in vitro with the diffusion method which was carried out in the MiCORE laboratory, Faculty of Dentistry, Universitas Trisakti. The independent variables were 5.25% NaOCl combination of 4% and 8.5% lansoprazole, 8.5% lansoprazole, 5.25% NaOCl combination of omeprazole 8.5%, 5.25% NaOCl and aquadest. Results: There was no inhibition zone of E. faecalis and E. coli in 8.5% lansoprazole, 5.25% NaOCl combination of omeprazole 8.5%, and aquadest. Inhibition zones of E. faecalis and E. coli were formed in 5.25% NaOCl combination of 4% lansoprazole, 5.25% NaOCl combination of 8.5% lansoprazole, and 5.25% NaOCl. The mean value of the inhibition zone of E. faecalis were 14,4±2,10 mm, 10,89±0,68 mm, and 25,9±1,46 mm respectively. Meanwhile, the mean value of the inhibition zone of E. coli were 19,48±2,48 mm, 10,89±0,76 mm, dan 30,22±1,10 mm. Conclusion: The antibacterial effect of 5.25% NaOCl combination of 4% and 8.5% lansoprazole was less effective than the antibacterial effect of 5.25% NaOCl.